1986
DOI: 10.1073/pnas.83.24.9458
|View full text |Cite
|
Sign up to set email alerts
|

Multiple controls of oxidative metabolism in living tissues as studied by phosphorus magnetic resonance.

Abstract: Three types of metabolic control of oxidative metabolism are observed in the various tissues that have been studied by phosphorous magnetic resonance spectroscopy. The principal control of oxidative metabolism in skeletal muscle is by ADP (or P1/phosphocreatine). This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(141 citation statements)
references
References 25 publications
4
137
0
Order By: Relevance
“…2). It is known from brain studies on animal models that it is pos sible to recognize stable and unstable states of me tabolism by knowing the ADP concentration (Clark et al, 1987;Delivoria-Papadopulos and Chance, 1988), the relationship between the rate of mito chondrial ATP biosynthesis and [ADP] having the characteristics of a rectangular hyperbola (Chance et al, 1985(Chance et al, ,1986. Therefore, an increased cytosolic free [ADP] indicates that the brain tissue operates nearer to the asymptote of the hyperbola and that brain cells are in a more unstable metabolic condi tion.…”
Section: Discussionmentioning
confidence: 99%
“…2). It is known from brain studies on animal models that it is pos sible to recognize stable and unstable states of me tabolism by knowing the ADP concentration (Clark et al, 1987;Delivoria-Papadopulos and Chance, 1988), the relationship between the rate of mito chondrial ATP biosynthesis and [ADP] having the characteristics of a rectangular hyperbola (Chance et al, 1985(Chance et al, ,1986. Therefore, an increased cytosolic free [ADP] indicates that the brain tissue operates nearer to the asymptote of the hyperbola and that brain cells are in a more unstable metabolic condi tion.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-consuming activity during muscular contraction (Chance et al, 1986;Katz et al, 1988) or during gluconeogenesis and ureogenesis (Tanaka et al, 1989), and upstream of the respiratory chain by reducing equivalent availability, i.e. dehydrogenase activity depending on the respiratory substrate metabolized (Berry et al, 1983;Nobes et al, 1990;Hassinen et al, 1990) and on calcium activation (Katz et al, 1988).…”
Section: Interactions Between Glucose Metabolism and Oxidative Phosphmentioning
confidence: 99%
“…We measured their activities under anaerobiosis and aerobiosis in the presence or absence of ethanol. the label at the level of fructose 1,6-bisphosphate by the action of aldolase and triosephosphate isomerase (den Hollander et al, 1979) and (b) the fructose-l,6-bisphosphatase activity (den Hollander et al, 1979(den Hollander et al, , 1986a. Using [l-"C]glucose or [6-'3C]glucose as substrate, it has been demonstrated that most of this scrambling is due to the aldolase and triosephosphate isomerase steps ; the contribution of the transaldolase pathway does not exceed 10% of the total for derepressed cells (den Hollander et al, 1986a).…”
Section: Atp-consuming Processes Linked To Glucose Metabolism Under Ementioning
confidence: 99%
“…47 Therefore, the differences in mitochondrial function ation of mitochondrial oxidative phosphorylation. [37][38][39] Therefore, the measurement of free ADP provides important infor-and ATP level between the two groups might be partly associated with the differences in the circulating TNF-a levels, mation with respect to the energy metabolism in the liver. Measurement of total ADP levels from tissue extracts overes-because enhanced TNF-a binding leads to reduction in circulating TNF-a levels in CK transgenic mice fed with creatine.…”
Section: Hours 48 Hours 72 Hours Dose Of Lps (Mg/kg) (%) (%) (%)mentioning
confidence: 99%